Research on the Enhancement of Student Work Competence in the Digital Age: A Case Study of Universities Affiliated to Zhejiang Province - Luo, Qing; Wang, Lexiao (Journal of Research in Vocational Education, 2025)
In the context of the rapid advancement of digitalization, the student affairs in institutions of higher education have encountered novel opportunities, while simultaneously being confronted with a succession of challenges. Student affairs workers in universities and colleges should be perceptive in discerning these changes, respond to them in a rational manner, and proactively utilize digital technologies to conduct ideological and political education. Against this backdrop, this paper delves into the challenges that student affairs workers face in their ideological and political work, and puts forward approaches to enhance their professional capabilities. By forging a new digital educational realm, establishing a new digital educational platform, and devising new digital educational methodologies, impetus can be provided for students’ growth and attainment of excellence. In the digital era, when dealing with student affairs, it is of utmost significance to remain true to the original aspiration of education. There should be a continuous improvement in the capacity to manage student affairs, integrating the traditional strengths of ideological and political education with new media and advanced technologies. This will contribute to enhancing the relevance and efficacy of ideological and political education, thereby providing comprehensive support for students’ holistic development.